Identify and Comparison of Handwriting Characteristics in Tamil and Malayalam - S Vinu Kumar,; Stiny Sabu, (International Journal of Scientific Research in Science and Technology, 2025)
Handwriting is writing that is done with a pen or pencil or any other writing material that is held by the hand. This study examines and compares the class and individual characteristics in two South Indian languages, Tamil and Malayalam. Tamil is considered the oldest language, and Malayalam is considered to have derived from the Tamil language. Identify and compare the similarities and differences in the handwriting characteristics of a single individual across both languages. A total of 150 handwriting samples in Tamil and Malayalam were gathered from 25 individuals from various age groups and different educational backgrounds. Each subject provided three samples in Tamil and three samples in Malayalam. The characteristics were examined qualitatively and statistically. The class and individual characteristics were identified and compared to determine the similarities and dissimilarities. The class characteristics were statistically analysed using a frequency test. This study aids in identifying the authenticity and authorship of the question document.
Keywords: class characteristics; handwriting; individual characteristics; Malayalam; Tamil